(untitled) (Praxis Educativa, 2017)
Throughout the history of the Argentine teacher training, many processes have gone through that have attempted to implement differentiated training projects with their own characterizations. It is possible to identify experiences that had different intentions of base, and varied intensities in their effects, but left traces that today survive in the institutions, in the provincial educational systems and in the subjects themselves. In this article we will especially recover the project “Poles de Desarrollo (2000-20001)” from the testimonies of the actors themselves and from the field of teacher training. We will use the biographical-narrative approach, since it gives us the possibility to reconstruct and reorganize the experience of the actors through the narrative, attributing meanings to the past with reference to the present and to the personal conceptions. This policy lacks visibility in Argentine academic productions and therefore constitutes the main object of our research.